FDXR is a biomarker of radiation exposure in vivo - O'Brien, Gráinne; Cruz-Garcia, Lourdes; Majewski, Matthäus; Grepl, Jakub; Abend, Michael; Port, Matthias; Tichý, Aleš; Sirak, Igor; Malkova, Andrea; Donovan, Ellen; Gothard, Lone; Boyle, Sue; et al. (Scientific reports, 2018)
Previous investigations in gene expression changes in blood after radiation exposure have highlighted its potential to provide biomarkers of exposure. Here, FDXR transcriptional changes in blood were investigated in humans undergoing a range of external radiation exposure procedures covering several orders of magnitude (cardiac fluoroscopy, diagnostic computed tomography (CT)) and treatments (total body and local radiotherapy). Moreover, a method was developed to assess the dose to the blood using physical exposure parameters. FDXR expression was significantly up-regulated 24 hr after radiotherapy in most patients and continuously during the fractionated treatment. Significance was reached even after diagnostic CT 2 hours post-exposure. We further showed that no significant differences in expression were found between ex vivo and in vivo samples from the same patients. Moreover, potential confounding factors such as gender, infection status and anti-oxidants only affect moderately FDXR transcription. Finally, we provided a first in vivo dose-response showing dose-dependency even for very low doses or partial body exposure showing good correlation between physically and biologically assessed doses. In conclusion, we report the remarkable responsiveness of FDXR to ionising radiation at the transcriptional level which, when measured in the right time window, provides accurate in vivo dose estimates.
Keywords: Young Adult; Male; biologické markery; počítačová rentgenová tomografie; Lipopolysaccharides; Middle Aged; Neoplasms; Up-Regulation; mladý dospělý; Biomarkers; lipopolysacharidy; kurkumin; Adult; upregulace; Aged; dospělí; mužské pohlaví; senioři; ferredoxin-NADP-reduktasa; Tomography, X-Ray Computed; senioři nad 80 let; lidé; RNA; ženské pohlaví; Humans; Aged, 80 and over; Curcumin; nádory; celotělové ozáření; Whole-Body Irradiation; Female; lidé středního věku; Ferredoxin-NADP Reductase